GC-MS assay of hexane and ethanol extracts of spirulina algae and detecting their antibacterial activity against uropathogenic S.aureus and E.coli - Salah Faiz Shnaa; Roaa J. Elkheralla; Mohammed Hashim Al-Yasiri (Počki)
Background. This study aims to assess the antimicrobial activity of spirulina hexane and ethanol extracts. The task is to discover standardized analytical methods for isolating original bioactive compounds from algae for fighting harmful bacteria such as E.coli and Staphylococcus aureus that cause urinary tract infections. Materials and methods. The study included the collection and preparation of spirulina algae from Nasiriyah, Iraq. The algae were cleaned, dried, and minced into powder. Twenty grams of the dried powder were mixed with 200 ml of ethanol and hexane solvents and subjected to ultrasonic extraction. The extracts were filtered and stored in sterile conditions. Antimicrobial activity was evaluated using varying concentrations (25, 50, 75, and 100 mg/ml) against bacterial strains Staphylococcus aureus and E.coli by the Kirby-Bauer disk diffusion method. Results. The ethanol extract showed the highest inhibitory effect against E.coli, with a zone of inhibition measuring 20.00 ± 2.00 mm at 100 mg/ml. It also showed inhibitory effect against S.aureus, with a zone of inhibition measuring 15.60 ± 1.51 mm at 100 mg/ml. The hexane extract showed significant activity against E.coli, with an inhibition zone of 17.60 ± 1.15 mm at 100 mg/ml, and exhibited inhibitory effect against S.aureus, with a zone of inhibition measuring 14.80 ± 1.30 mm at 100 mg/ml. Then the activity decreased for both extracts with a reduction in concentration. Comparative analysis demonstrated that both extracts outperformed several tested antibiotics in terms of efficiency against the respective bacterial strains. Conclusions. The findings indicate that algae extracts have significant antimicrobial properties, making them potential alternatives to conservative antibiotics in treating urinary tract infections. The study highlights the importance of these extracts in emerging specific preparations from algae for antimicrobial applications, contributing to the field of alternative medicine.